(untitled) (Research, Society and Development, 2020)
The objective of the study was to investigate food production in the communities of Braúnas and Lagoa da Pedra, municipality of Diamantina, Minas Gerais, Brazil. There were 44 dwellings in the communities, 36 in which we conducted interviews through a structured questionnaire. 120 people lived in these houses, 57 of which were female and 63 male. Among the interviewees, 26 mentioned having the habit of growing vegetables in a vegetable garden in the home environment, mainly for self-consumption. The cultivation of food in backyards, but outside the garden space, was mentioned by 35 interviewees. Plantations were also observed in “swiddens” located in floodplain areas in the floodplains of the Jequitinhonha River, with beans, corn and rice being the main cultivated foods. In the harvest prior to the study, in 2015, a production of 67.14 tons of beans, 10 tons of corn and 360 kilos of rice was estimated. The production of beans has the commercialization as its main purpose, and this product leaves the community through middlemen. For the cultivation and harvesting of food in “roças”, some families reported hiring temporary workers. Given the tradition of agricultural production in these communities, and with the recent creation of the Parque Nacional das Semper Vivas, where the areas used by the residents of the communities to live, carry out their plantations, animal husbandry and extractivism, were located within the buffer zones of this Conservation Unit, it is important to maintain good relations between Conservation Unit managers and community leaders so that cultural practices and biodiversity are respected by both parts.